PHYTOCHEMICAL INVESTIGATION AND IN VITRO ANTIOXIDANT ACTIVITY OF SYZYGIUM JAMBOS FRUIT AND ITS SEED - DUTTA, SUCHANDRA; HALDER, SHREYASI; KHALED, KAZI LAYLA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study was designed to investigate the phytochemical screening of different solvent extracts, total phenolic, and flavonoid content and 13 different methods of in vitro antioxidant activity of Syzygium jambos fruit and its seed. Methods: The antioxidant activity of the methanolic extract of S. jambos fruit and its seed was carried out by 2,2-diphenyl-1-picrylhydrazyl, ABTS radical scavenging activity, site-specific and non-site-specific hydroxyl radical scavenging activity, superoxide radical scavenging, nitric oxide radical scavenging, potassium ferricyanide reducing assay, ferric thiocyanate, total antioxidant capacity, hydrogen peroxide radical scavenging, thiobarbituric acid reactive substances, ferric reducing antioxidant power, and cupric reducing antioxidant Cusing standard procedures. Results: The preliminary phytochemical screening has revealed the presence of phenolics, flavonoids, alkaloids, tannin, saponin, and carbohydratesexcept for steroids and terpenoids. The total phenolic content and flavonoid content of S. jambos fruit and its seed was found to be (S. jambos fruit – 127.61 mg of GAE/100 g, S. jambos seed – 217.34 mg of GAE/100 g) and (S. jambos fruit – 8.64 mg of QE/100 g, S. jambos seed – 15.97 mg of QE/100 g), respectively. The fruit and its seed also showed significantly strong antioxidant activity in different in vitro methods. Conclusion: The Syzygium jambos fruit and its seed have anadequate quantity of phytochemicals that act as an antioxidant and scavenge free radicals efficiently. Hence, the fruit and its seed may be considered as effective in the prevention and treatment of oxidative stress-induced diseases such as diabetes, cardiovascular diseases, cancer, arthritis, gout, neurodegenerative diseases, and respiratory tract infections.